Probable mental illnesses among tea plantation workers in Anaimalai, Tamil Nadu, South India - G. S., Ashwini; Ramesh, Naveen; C. J., Navya; Joy, Jino; Oommen, Abel Thomas; Singh, Jyoti (International Journal Of Community Medicine And Public Health, 2017)
Background: The prevalence of mental illnesses among industrial workers is found to be 14% - 51%, which is more than that in the general population. Individual’s psychosocial functioning has an impact on the work efficiency. The objective of the study was to assess the prevalence of probable mental illness and its associated factors among workers in selected tea estates in South India. Methods: A cross sectional study was done in two tea estates in Tamil Nadu from March to May, 2012. The General Health Questionnaire (GHQ) 28 was used to screen for probable mental illness. Sociodemographic details, work profile and associated risk factors were also elicited. Results: Among the 400 subjects interviewed, 75.5% were females. The mean age was 43.21 (±7.47) years and the mean work experience was 21.38 (±9.31) years. In our study 12.8% subjects screened positive for probable mental illness and 1%, 1%, 0.2% and 1.5% screened positive in the domains somatic symptoms, anxiety/insomnia, social dysfunction and severe depression respectively. Workers who screened positive for probable mental illness had availed significantly greater duration of leave in the previous year. There was no significant association of mental illness with age, gender, marital status, substance abuse, designation, co-morbidity and stressful life events. Conclusions: There is a need to screen individuals in different occupation for probable mental illness and those screened positive need evaluation by a psychiatrist. There is also a need to explore associated factors in order to improve one’s health and work efficiency.